2009
DOI: 10.1590/s1413-70542009000700005
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação da uniformidade de aplicação de água em um sistema de gotejamento para pequenas propriedades

Abstract: RESUMOO uso de sistemas de irrigação por gotejamento à baixa pressão tem como objetivo oferecer uma técnica de irrigação viável para pequenas propriedades. Foram dimensionados oito sistemas de irrigação, um com os seguintes acessórios: 210 metros de tubo gotejador com diâmetro interno (DI) de 10,4 mm, sete conectores de 12 mm, e seis metros de tubo de polietileno, um adaptador para tubo de polietileno, uma curva de 90º e três metros de tubo de PVC com DI igual a 20,6 mm. Quatro sistemas foram montados com um f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 5 publications
0
3
0
1
Order By: Relevance
“…Furthermore, its pumping requires less energy, it potentially minimizes negative irrigation impacts on soil, and facilitates the use of fertigation (Nascimento et al, 2009). Nonetheless, a study of the basic principles of water and fertilizer management is essential for sustainable irrigated agriculture (Bernardo et al, 2008), as well as the amount of water required for best efficiency (Harmanto et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, its pumping requires less energy, it potentially minimizes negative irrigation impacts on soil, and facilitates the use of fertigation (Nascimento et al, 2009). Nonetheless, a study of the basic principles of water and fertilizer management is essential for sustainable irrigated agriculture (Bernardo et al, 2008), as well as the amount of water required for best efficiency (Harmanto et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Research has shown that when deficit irrigation compared to full or sprinkler irrigation is applied together with N-fertilizer in solution, an increase in total soluble solids (TSS) in tomato is observed (Wang et al, 2015) and the drip irrigation favours more uniform water distribution in the tomato plant, increased plant yield and reduced evapotranspiration (Ozbahce and Tari, 2010). In addition, the pumping under drip irrigation unlike full or sprinkler irrigation requires less energy and potentially minimizes negative irrigation impacts on soil such as waterlogging or erosion and facilitates the use of fertigation (Nascimento et al, 2009). Grewal et al (1990) showed that the difference between soil moisture held at field capacity and the wilting point (total available soil water), governs amongst other factors, the growth of a plant.…”
Section: Introductionmentioning
confidence: 99%
“…Segundo Nascimento (2009a), devem-se desenvolver alternativas para difundir a irrigação para agricultura familiar, por proporcionar o aumento da produção, geração de emprego e renda e, consequentemente, diminuir o êxodo rural. Existem diversas tecnologias alternativas utilizadas na irrigação a custos mais baixos que podem propiciar a sua adoção por agricultores com pequeno poder financeiro, uma delas é o sistema bubber (COELHO et al, 2012a,b).…”
Section: Introductionunclassified